Electronic energy loss of channeled ions : the giant Barkas effect - Araújo, Leandro Langie (2004)
In this work we have measured the electronic energy loss of ⁹Be and ¹¹B ions for the ‹100› and ‹110› directions in Si as a function of the incident ion energy. The channeling measurements cover a wide energy range between 100 keV/amu and 1 MeV/amu. The Rutherford backscattering technique has been employed in the present experiments. An overall compilation of channeling energy loss values for several ions, including those for He, Li, and O measured previously, provides a clear picture of the Barkas contribution to the stopping power due to valence electrons in the present energy regime. A maximum of the relative contribution occurs for Be ions around 250 keV/amu while a saturation effect is observed for heavier ions. These results are interpreted in terms of a self-consistent nonlinear calculation based on the transport cross-section approach together with the unitary convolution approximation model, which describe the present data reasonably well at high projectile energies.